Rio de Janeiro 2016 Aplicant City (Rio2016, 2008)
The 2016 Rio project is moving full steam ahead. The marvelous city plans open-air competitions during the 16 days of the Olympic Games. The objective is to explore Rio's rich nature to the utmost and provide a unique event, a celebration of beauty and the importance of sports.